Computational methods in molecular imaging technologies - Gunjan, Vinit Kumar; Shaik, Fahimuddin; Venkatesh, Chethan; Amarnath, M. (Springer, 2017)
This book highlights the experimental investigations that have been carried out on magnetic resonance imaging and computed tomography (MRI & CT) images using state-of-the-art Computational Image processing techniques, and tabulates the statistical values wherever necessary. In a very simple and straightforward way, it explains how image processing methods are used to improve the quality of medical images and facilitate analysis. It offers a valuable resource for researchers, engineers, medical doctors and bioinformatics experts alike.
Keywords: Diagnostic imaging.; Imaging systems in medicine.; Computational intelligence.; Computational biology.; elektronické knihy; electronic books